(untitled) (Research, Society and Development, 2022)
Paralympic Boccia (BP) is a sport that assists people with severe physical disabilities, including people with cerebral palsy (CP), whose social interaction and communication may be flawed. In this sport, athletes with communication difficulties can produce a lower sports performance, as they are not able to convey their needs clearly. To increase communication channels during game tasks, was the objective of this study. The research, divided into two phases, had the participation of 27 BP athletes. In Phase 1, 25 athletes responded to an online form, with 69 phrases used by them to communicate in a game. In Phase 2, five athletes, among which three also participated in Phase 1, used the PGCA system. The data showed that the most frequent phrases are greeting and farewell phrases, and some discussion phrases related to the game. In Phase 2, the PGCA system built an image, considering the speed of the gesture and the body segment used for its execution, which was interpreted and the corresponding sentence was pronounced. In the final stage of the research, the effectiveness of 22% in gesture recognition, the efficiency of 12.80s for the system to recognize the gestures and pronounce the corresponding frase and the good usability for the context of the study, favor indications for an active participation with greater autonomy of these athletes, providing also new experiences of accessibility to BP, pedagogical teaching and paralympic sports education.